The role of polyphenols in controlling periodontal inflammation: a systematic review - Dario Di Nardo; Laura Sarnelli; Gabriele Miccoli; Francesca Romana Stanganelli Federici; Almira Isufi; Edit Xhajanka; Roberta Grassi (Annali di Stomatologia)
Introduction: Recent research has explored the therapeutic potential of polyphenols, natural compounds with antioxidant, antimicrobial, and antiinflammatory properties, in modulating host responses to periodontal disease. This systematic review examines the impact of various polyphenols—including ellagic acid (pomegranate), catechins (green tea), curcumin, resveratrol, propolis, and quercetin—on periodontal health. Materials and methods: A bibliographic search was conducted using Medline-PubMed with the following keywords: “(GSE) AND (periodontitis)”; “(quercetin) AND (periodontitis)”; “(catechin) and (periodontal)”; “(punica granatum) and (periodontitis)”; “curcumin and periodontitis”; “ellagic acid and periodontitis”; “epigallocath and periodontitis”; “phenols and periodontitis”; “polyphenols and periodontitis”; “propolis and periodontitis”; “resveratrol and periodontitis.” No timeline restrictions were applied. Articles regarding Bleeding Index (BI), Bleeding Point Index (BPI), Gingival Bleeding Index (GBI), Modified Gingival Index (MGI), Oral Hygiene Index (OHI), Simplified Oral Hygiene Index (OHI-S), Plaque Control Record (PCR), Plaque Index (PLI), Relative Attachment Loss (RAL), Sulcus Bleeding Index (SBI), Tooth Mobility (TM), Visible Plaque Index (VPI) were included. Microbiological parameters such as colony-forming units (CFUs) and microbial counts of S. mutans, P. gingivalis, T. forsythia, and T. denticola were also included. Results. A total of 405 articles were identified following the conducted searches as described above. After the removal of duplicates, 399 articles were further examined based on their title and abstracts. Of these, 207 were excluded after title review. A total of 192 abstracts were then screened, and 147 were excluded. As a result, 45 full-text studies were assessed for eligibility. A total of 30 studies remained and were included in the final analysis. Of these 30 studies, 8 focused on ellagic acid or pomegranate (where the molecule of interest is ellagic acid), 8 examined catechins, 5 investigated curcumin, 5 were related to propolis, 2 explored resveratrol, and 1 study each addressed GSE (grape seed extract) and quercetin combined with apigenin and gallic acid. Conclusions: Polyphenols present a viable adjunct or alternative to conventional periodontal treatments, offering benefits in both local and systemic inflammation management. Their incorporation into dietary and oral hygiene regimens could enhance periodontal health and overall patient well-being. Future research should focus on refining formulations, determining optimal dosages, and evaluating their long-term clinical effectiveness in personalized periodontal treatment strategies.